‘Show Us a Kiss!’: The Everyday Sexual Harassment Experiences of Female Lesbian, Bisexual, and Queer Students - Witcomb, Gemma L. (Violence against women, 2024)
This study explored the experiences of lesbian, bisexual, and queer (LBQ) students’ (N = 9, aged 19–24) of sexual harassment via semistructured interviews. Data were analysed using a thematic analysis. Three overarching themes emerged: (a) the paradox of men's unwanted sexual attention, (b) the negative impact on relationships, and (c) the LGBTQ* community as a refuge. The women reported enduring unwanted heteronormative sexual attention, and heterosexist and homophobic harassment which forced some to conceal their sexuality. Support for the LGBTQ* community was central in developing confidence to call-out harassment. The findings call for the inclusion of LBQ-specific messages in sexual violence awareness and prevention interventions.